Exploring the usefulness of public relations in an academic institution case study of the Holy Trinity College of General Santos City - Tingzon, Phoebe G.
Chiefly guided by the Agenda-setting theory of McCombs and Shaw, this study investigated the usefulness of public relations in an academic institution. This was implemented to ascertain the core agenda of the Holy Trinity College of General Santos City in utilizing public relations. As attested by the respondents, it was found out that the school uses public relations to create a good name that is capable of attracting the public, to encourage the parents to enroll their children in the school and to solicit support from the government and from private institutions. Furthermore, the researcher aimed to know the objectives of the school in producing a certain tool and to determine if the tool is able to deliver or reinforce the objective assigned to it. The tools that were investigated were only those that were most useful as perceived by the respondents. The billboards, tarpaulins and a brochure completed the list of these of these tools. As these tools had been identified, the researcher made an extensive assessment of each by considering the tool's language and visuals. From the direct investigation made, it was discovered that the billboards, tarpaulins and brochures were all capable of delivering and reinforcing their objectives. As for the billboards, they are useful in introducing the school to the public. The tarpaulins of five different variants aid in highlighting the achievements of the school's employees and students as well as in giving announcements to the public. Lastly, the brochure assists the school in letting the public know of the school's specific programs and services.